PENURUNAN TINGKAT KESUBURAN AKIBAT ALAT KONTRASEPSI - Nuke Devi Indrawati; Dewi Puspitaningrum; Indri Astuti Purwanti (Jurnal Ilmu Keperawatan dan Kebidanan, 2018)
Servicitis Cronica is an early stage of cervical cancer, which is a cancer that is developing organ in Indonesia. If Servicitis Cronica can be prevented earlier, the likelihood of cervical cancer incidence can be reduced significantly (long term).The type of analytic study with a total sample of 116 women of childbearing age.Parity variables, family planning and education are the only two variables, namely parity (0,012) and KB (0,035) because its significance is less than 0,05. The most influential variable is the parity variable because the smallest signification is 0.012.Keywords: servicitis cronica, IVA test, Female Age Fertile